Universities that matter for regional knowledge base renewal: The role of multilevel embeddedness - Nils Grashof; Holger Graf (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
We analyze the role of universities or, more generally higher education institutions (HEIs), in terms of their regional and international embeddedness for regional knowledge base renewal. We assume that the introduction of radical patents in the sense of novel technological combinations contributes to the renewal of the knowledge base. For our empirical study, we combine information from patent applications, scientific publications and higher education statistics. We find that HEIs contribute most to knowledge base renewal if they have a strong research output and are locally embedded. International research embeddedness of HEIs benefits regional development only if combined with a central position in the regional network.
Keywords: I20; I23; I25; O3; R11; 330; higher education institutions; universities; knowledge base renewal; radical innovation; SNA; embeddedness